Towards a knowledge-based society: the need for a continuous lifelong - Correia, Ana Maria Ramalho (2012)
IRMA International Conference under the theme Managing Worldwide Operations and Communications with Information Technology, May 19-23, Vancouver, British Columbia, Canada